Evangelicals : who they have been, are now, and could be - Noll, Mark A., 1946-; Bebbington, David, 1949-; Marsden, George M., 1939- (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2019)
"This books draws together significant considerations of evangelicalism from three of the historians who have contributed a great deal to putting the subject on the map, along with selected commentary from others who have benefited from, or sometimes questioned, their work"--
Includes bibliographical references and index.
Keywords: Evangelicalism